SEED DETERIORATION PATTERN OF FOUR BAMBARA GROUNDNUT LANDRACES (Vigna subterraneasubterranean (L) Verdc) IN OPEN STORAGE SYSTEM - Hamami, Happy Suryati; Qadir, Abdul; Ilyas, Satriyas; Budhianto, Bambang (Informatika Pertanian, 2018)
Bambara groundnut (Vigna subterranea (L.) Verdc) is a potential commodity to be developed in Indonesia, however, the production is done only once a year, therefore, it needs proper seed storage. The aim of this research was to study seed deterioration patterns of four bambara groundnut landraces stored in packages with different permeability in an open storage system for up to 6 months. This experiment was conducted from November 2015 to July 2016 at Seed Technology Laboratory, Department of Agronomy and Horticulture, IPB. Stages of experiment as follow: calculation of packaging permeability, seed storage, preparation and fitting data to regression equation.The packaging used in the study is aluminum foil, pp plastic and plastic sacks which have measured its permeability. The result showed that the seed deterioration of four bambara groundnut landraces in three packaging permeability has common sigmoidpattern with equation model: y = a / {1 + exp ((x + b) / c)}. The seed deterioration pattern based on SG and EC variables with the faster rate of decline occurred in Sumedang landrace packed in plastic sack (permeability = 1.4681 g/day m2 mm/Hg), thus having a shorter storability. The slower rate of decline occurred in Gresik landrace packed in aluminum foil (permeability = 0.098 g/day m2 mm/Hg), this means that it has a longer storability.